Strategies for indica rice adapted to high-temperature stress in the middle and lower reaches of the Yangtze River - Zhang, Man; Li, Zhong; Feng, Kaixuan; Ji, Yalan; Xu, Youzun; Tu, Debao; Teng, Bin; Liu, Qiumeng; Liu, Jingwen; Zhou, Yongjin; Wu, Wenge (Frontiers in Plant Science, 2023)
High temperatures caused by climate warming severely affect the grain yield and quality of rice. In this study, the rice cultivars Longliangyou Huazhan (LLYHZ) and Quanliangyou 2118 (QLY2118) were selected as the experimental materials for investigation of an optimal cultivation system under high-temperature treatment. In addition, the heat-resistant cultivar Huanghuazhan (HHZ) and heat-sensitive cultivar Huiliangyou 858 (HLY858) were chosen as the experimental materials to study the effects of exogenous plant growth regulators on heat stress responses under high-temperature treatment. The results showed that mechanical transplanting of carpet seedlings and delayed sowing effectively increased the leaf area index and reduced the canopy temperature of LLYHZ and QLY2118. Furthermore, carpet seedling mechanical transplantation and delayed sowing improved grain yield and quality. Spray application of five plant growth regulators revealed that brassinolide and salicylic acid had the strongest effects on significantly improving antioxidant enzyme activities in the panicle, which would reduce the damage caused by the accumulation of reactive oxygen species and enhance plant tolerance of high-temperature stress. In addition, brassinolide and salicylic acid enhanced the percentage of anther dehiscence and percentage seed set. In this study, a set of simplified eco-friendly cultivation techniques for single-season indica rice adaptation to high-temperature stress was established. These results will be of great importance in alleviating the effects of high-temperature stress on rice production.